Yeast plasma membrane Fungal Oligopeptide Transporters display distinct substrate preferences despite their high sequence identity - Becerra-Rodríguez, Carmen (2021)
Fungal Oligopeptide Transporters (Fot) Fot1, Fot2 and Fot3 have been found in Saccharomyces cerevisiae wine strains, but not in strains from other environments. In the S. cerevisiae wine strain EC1118, Fot1 and Fot2 are responsible for a broader range of oligopeptide utilization in comparison with strains not containing any Fot. This leads to better fermentation efficiency and an increased production of desirable organoleptic compounds in wine. Despite the benefits associated with Fot activity in S. cerevisiae within the wine environment, little is known about this family of transporters in yeast. The presence of Fot1, Fot2 and Fot3 in S. cerevisiae wine strains is due to horizontal gene transfer from the yeast Torulaspora microellipsoides, which harbors Fot2Tm, FotX and FotY proteins. Sequence analyses revealed that Fot family members have a high sequence identity in these yeast species. In this work, we aimed to further characterize the different Fot family members in terms of subcellular localization, gene expression in enological fermentation and substrate specificity. Using CRISPR/Cas9, we constructed S. cerevisiae wine strains containing each different Fot as the sole oligopeptide transporter to analyze their oligopeptide preferences by phenotype microarrays. The results of oligopeptide consumption show that Fot counterparts have different di-/tripeptide specificities, suggesting that punctual sequence divergence between FOT genes can be crucial for substrate recognition, binding and transport activity. FOT gene expression levels in different S. cerevisiae wine strains during enological fermentation, together with predicted binding motifs for transcriptional regulators in nitrogen metabolism, indicate that these transporters may be under the control of the Nitrogen Catabolite Repression (NCR) system. Finally, we demonstrated that Fot1 is located in the yeast plasma membrane. This work contributes to a better understanding of this family of oligopeptide transporters, which have demonstrated a key role in the utilization of oligopeptides by S. cerevisiae in enological fermentation.